The phase of darkness – measuring the phase of a dark pulse - Brunzell Martin; Oxelmark Krook Christoffer; Laurell Fredrik; Pasiskevicius Valdas (EPJ Web of Conferences)
Dark optical solitons are solutions to the nonlinear Schrödinger equation in normal dispersion media with positive Kerr nonlinearity, exhibiting a discrete π phase jump. These solitons are valuable to applications within telecommunication. Recent advancements have demonstrated the generation of two-colour bright-dark soliton pairs through cross-amplitude modulation in laser cavities, resulting in mode locking. In this study we present for the first time full field characterization of the electric field of a dark pulse. We achieved this by performing Blind Frequency Resolved Optical Gating measurements using the synchronous bright pulse as the gate pulse. The retrieved dark pulse verifies the existence of the expected π phase jump in the phase of the dark pulse, confirming theoretical predictions.